Effect of nitrogen, phosphorus, potassium, and sulphur on the growth and seed yield of coriander (Coriandrum sativum L.) (Bangladesh Journal of Agricultural Research, 2014)
A field experiment was conducted at the Spices Research Centre, Shibgonj, Bogra, Bangladesh during the rabi seasons of 2008-2009 and 2009-2010 to determine the requirement of N, P, K, and S of coriander (BARI Corinader-1) for achieving satisfactory seed yield of this crop. Different levels of nitrogen (0, 40, 70, and 100 kg/ha), phosphorus (0, 25, 50, and 70 kg/ha), potassium (0, 30, 60, and 90 kg/ha), and sulphur (0, 10, 20, and 30 kg/ha) were distributed in the plot. The experiment was tested in randomized complete block design with three replications. There was positive impact of application of those nutrients on the yield and yield contributing characters of coriander up to a moderate level of N70P50K30S20 kg/ha. The highest seed yield (2.06 t/ha in 2008-2009 and 2.09 t/ha in 2009-2010) was obtained with this moderate application of N, P, K, and S (70, 50, 30, and 20 kg/ha, respectively) and yield was declined with higher doses of these elements. The fertilizer treatment N70P50K30S20 was observed to be the best suitable dose for coriander cultivation on Grey Terrace Soil of Amnura Soil Series under AEZ-25(Level Barind Tract) of Bangladesh. DOI: http://dx.doi.org/10.3329/bjar.v39i2.20433 Bangladesh J. Agril. Res. 39(2): 303-309, June 2014